Zarządzanie ryzykiem kredytowym na podstawie firmy ubiegającej się o kredyt inwestycyjny - Mendel, Rafał (My University, 2011)
Loan activity is a classic domain of commercial banks, and it is a loan, this main bank product, that constitutes the most important source of generating profits. Issuing loans involves credit risk that can pose a danger for the bank. The scale of credit risk may be minimized by banks implementing risk management systems based on the assessment of the potential debtor’s creditworthiness, which in turn is used to decide whether to grant the credit or not. In order to portray the methodology of credit risk assessment applied by major commercial banks in Poland, the creditworthiness of a company applying for an investment loan was examined. According to the hypothesis that was made, the economic and financial condition of this company allowed it to pay off the bank loan with interest. Having received a very good score in a point assessment scale of the criteria that were used to appraise the economic condition of the company, the company was qualified into the internal banking class of very low risk, which allowed it to be granted the amount of loan that had been applied for. The aim of creditworthiness assessment is to establish whether the current as well as the future financial condition of the potential debtor will allow them to pay off the debt to the bank, and it constitutes the basis for the loan application procedure.

Działalność kredytowa jest klasycznym obszarem działania banków komercyjnych a kredyt, jako główny produkt bankowy stanowi główne źródło generowania dochodów. Udzielanie kredytów związane jest z niebezpieczeństwem dla banku, jakim jest ryzyko kredytowe. Jego rozmiary są minimalizowanie poprzez wprowadzenie przez banki systemu zarządzania ryzykiem, którego fundamentem jest ocena zdolności kredytowej potencjalnego kredytobiorcy, decydująca o przyznaniu kredytu lub jego odmowie. W celu przedstawienia metodyki oceny ryzyka kredytowego stosowanego w największych bankach komercyjnych w Polsce, poddano badaniu zdolność kredytową firmy ubiegającej się o kredyt inwestycyjny, stawiając hipotezę, że jej sytuacja ekonomiczno-finansowa pozwala na spłatę kredytu wraz z odsetkami. Uzyskując bardzo dobry wynik z oceny punktowej kryteriów oceniających kondycję ekonomiczną firmy, została ona zakwalifikowana do wewnątrzbankowej klasy ryzyka bardzo niskiego, co wiąże się z otrzymaniem wnioskowanej kwoty kredytu. Ocena zdolności kredytowej służy ustaleniu, czy bieżąca i przyszła sytuacja finansowa kredytobiorcy pozwala na terminową spłatę długu wobec banku i stanowi ona podstawą procedury ubiegania się o kredyt.
Credit risk management on the example of a company applying for an investment loan
Keywords: bank; kredyt; ryzyko kredytowe; zdolność kredytowa; zarządzanie ryzykiem; credit risk; loan; creditworthiness; risk management